Measuring the Local Economic Impacts of Replacing On-Street Parking With Bike Lanes: A Toronto (Canada) Case Study. Issue 4 (2nd October 2019) - Arancibia, Daniel; Farber, Steven; Savan, Beth; Verlinden, Yvonne; Smith Lea, Nancy; Allen, Jeff; Vernich, Lee
Abstract: Problem, research strategy, and findings: Bike lane projects on retail streets have proved contentious among merchant associations in North America, especially when they reduce on-street parking. A limited but growing number of studies, however, detect neutral to positive consequences for merchants following bike lane implementation. In 2016, the City of Toronto (Canada) removed 136 on-street parking spots and installed a pilot bike lane on a stretch of Bloor Street, a downtown retail corridor. Using a case–control and pre–post design, we surveyed merchants and shoppers to understand the impacts of the bike lanes on economic activities. We find no negative economic impacts associated with the bike lanes: Monthly customer spending and number of customers served by merchants both increased on Bloor Street during the pilot. Takeaway for practice: Our findings are consistent with an improving economic environment at the intervention site. Downtown retail strips may therefore be suited to tolerate bike lanes and even benefit from increased retail activity. Pre and post surveys can provide valuable insights into local economic impacts of streetscape changes affecting merchants along city streets, especially where access to sales data is limited.